The Total Economic Costs of Road Accidents in Libya - شامية, عبدالله (Dirasat in Economics and Business, 2008)
This paper aims to estimate the total economic costs of road accidents in Libya utilizing actual data for 2007, the study uses a well-known analytical framework that focus on the normative ( ex-ante ) approach - what ought to be, and the positive ( ex-post ) approach – what is, and classify these costs into different items according to origin by using the Transport Research Laboratory (TRL) of the United Kingdom measures of costing road accident for developing countries. Costing will include costs incurred by the victim, the family, the related institutions, and the society in general. Measuring emotional damages translated to social costs puts values to non-monetary terms such as the pain, grief and suffering (PGS) of the victim and the affected family. These are things not bought nor sold, otherwise known as nonmarket values. Though debatable, it becomes essential to justify accident reduction measures and traffic improvement policies in order to create awareness and effective decision-making. The approach classifies accident cost into three main components: Victim related costs are directly associated with the resources lost of the casualties. To be humane and considerate of the social impacts of accidents, a notional sum is also added to quantify the PGS of the victim's families. Property damage consists of vehicle repair, lost of economic productivity of public utility vehicles and cost of towing services. The first two components make the largest portion of property damage and are given due attention in this paper. Costs associated with police investigation,legal activities and insurance administration. Total number of road accidents that occurred in the Libyan society during 2007 reached 13165 accidents, resulted in the death of 2138 persons, and seriious injuries to over 13497 persons, and caused damages to The total economic costs are estimated to be over 1.485 billion Libyan dinars during 2007; the main results of the study are summarized in the following table. The study presents a set of measures that we think are most effective in controlling the problem, and suggests the adoption of a long-run strategic plan to fight such an epidemic.